Fabric Mulch for Tree and Shrub Plantings - Atchison, Robert L. (My University, 2004)
This publication describes the specifications for using fabric mulch when planting trees and shrubs.
MF2216_2004_08
Keywords: MF2216; Forestry; Lawn and Garden; MF